Study of the Economic Value of Waste Recycling Concept in Supporting Sustainable Development Goals (SDGs) Program in TPA Kabinuang, Tolitoli Regency - Edi Yanto; Bustam Bustam; Aqfir Aqfir (IJEBD (International Journal of Entrepreneurship and Business Development), 2021)
This type of research is a descriptive study with a quantitative approach that aims to determine the economic value of waste through the concept of recycling to support the SDGs program for sustainable economic improvement. The results showed that the total composition of waste in TPA Kabinuang Tolitoli consisted of 35% inorganic waste and 65% organic waste. The types of waste that can be recycled include kitchen waste, leaves and plants, plastic, paper, cloth, rubber, glass, wood, and iron. If accumulated, as much as 100 kg of solid waste based on its type generates an economic value of IDR 270,400. This economic value becomes the basis, reference and encouragement for the community to be able to sort waste in order to improve the community's economy in a sustainable manner.